Penerapan Sanitasi Pada Salon Hadi & Co Di Kelurahan Sekaran, Kecamatan Gunungpati - Nurul Safitri; Mardhiyya Nayla Yusuf; Arifa Nayla Nugrahanti; Filla Himatul Falla; Azra Jenar Mas; Manik Ayu Cahyaningtyas; Saskia Asha Subekti; Bening Sejati Istiqomah; Eny Widhia Agustin; Mia Hafizah Tumangger (Jurnal Sanitasi Profesional Indonesia, 2025)
Sanitation is a critical aspect of public health, particularly in high-contact environments like beauty salons, where hygiene directly impacts both customer safety and staff well-being. This study aims to assess the sanitation practices at Hadi & Co Salon, located in Sekaran Village, Gunungpati District, Semarang City. Utilizing a qualitative descriptive approach, data were collected through interviews and direct observations in May 2025. Three respondent groups were involved: salon owners, beauticians, and customers, providing a comprehensive perspective on the implementation of sanitation measures. The findings indicate that overall, the sanitation practices at Hadi & Co Salon are well-implemented, though further improvements in waste management and building maintenance are necessary to meet higher health and safety standards.